KISAH PERANG BADAR (Studi Nilai dalam Suatu Masyarakat) - Elhany, Hemlan (JURNAL TARBAWIYAH, 2014)
The values of Badar War is the esential of the event in the war occur. If we look at the Physical aspects, the objective condition of moeslem when the war occur, itâs out of the line to make the opponent lost, because they have many soldiers with strong tool army. In other side, the moslem have little soldier and little tool army. The moeslem army does not have good spirit to go to the war, because the opponent have many soldiers. More over, they only go to the war with the materialistic spirit not follow the instruction from Rosullullah as the leader of moslem. Essentially, if every moslem do every instruction from the Allah and Rosul, they can win in the Badar War. In the promise of Allah that will give the relief and victory.Key Words: Perang Badar, Nilai, dan Masyarakat